Women's empowerment and current contraceptive use in Pakistan: informed by theory of gender and power - Kumari, Bhavita; Do, Mai; Madkour, Aubrey Spriggs; Wisniewski, Janna Marie (Frontiers in Global Women's Health, 2024)
IntroductionIt is evident from the stagnant modern contraceptive rate and the growing population of Pakistan that the family planning (FP) programs in Pakistan have failed to deliver successfully. The study examines the association of domains of women's empowerment, following the Theory of Gender and Power, with the current use of contraceptive methods and how intimate partner violence (IPV) can moderate such associations in Pakistan.MethodsMarried women of reproductive age from the Pakistan DHS (2017–18) were included in the analysis (n = 14,502). Key independent variables were identified using Connell's Theory of Gender and Power operationalized by Wingood and DiClemente, and constructs were created using principal component analysis. Multinomial logistic regressions were conducted to assess the relationships of the three empowerment divisions (i.e., sexual division of labor, sexual division of power, and cathexis), to the current use of contraceptives.ResultsWhen all empowerment domains were included in the model along with covariates, education (sexual division of labor), sex negotiations (sexual division of power), and husband's fertility intentions (cathexis) remained significant in their associations with modern contraceptive use.ConclusionThis is the first study in Pakistan to examine multi-faceted empowerment, applying Connell's theory of gender and power to identify key domains associated with contraceptive use. A multi-prong approach to FP programs that aims to improve specific domains of women's empowerment and to increase FP service use may be more likely to succeed than stand-alone programs.